The Effectiveness of Using Video as Learning Media for Listening Comprehension in Narrative Text - Rizqadifa Shaden (Retain: Journal of Research in English Language Teaching, 2024)
Listening is the capacity to pay attention to and comprehend what other people are saying. One of the most exciting activities that improve listening skills is watching movies. One movie genre that is very safe for students to consume is the fairy tale. The fairy tale movie is currently being adopted through old cartoon movies and updated with human versions with more interesting storylines but still have moral values. The research design used for this study is Pre-experimental. The data collected was listening material. The listening material has been adapted from the children's story Alice in Wonderland. Moreover, I lead to the aims of this research are to find out the significant enhancement in terms of generic structure in narrative text and to find out the significant enhancement in terms of delivered message in narrative text. The researcher implemented a quantitative research design and this study involved ninth-grade students, 18 of whom were boys and 18 of whom were girls. There are changes in the pre-test and post-test scores regarding the generic structure of the narrative text. The score that changed from the first question reached 97% and in the second question 93.9%. The results showed a notable rise in the post-test score average from 72.79 to 88.82, signifying the effectiveness of incorporating videos as a learning tool. The study concluded that the use of video significantly enhanced students' listening comprehension skills and facilitated their understanding of narrative texts.